ASSOCIATION BETWEEN MENARCHE AGE AND MENOPAUSAL SYMPTOMS - R, Muharam; Ikhsan, Muhammad; Rizkinya, Herdinda Erudite (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this study was to assess the association between menarche age and menopausal symptoms. Methods: A cross-sectional study with 100 perimenopause subjects. Every subject was assessed of their menopausal symptoms with validated menopause rating scale (MRS) questionnaire. Menopause symptoms were classified into somato-vegetative, psychological, and urogenital symptoms. Statistical analysis was used to assess menarche age and menopause symptoms associations. Results: Out of 100 subjects, somato-vegetative, psychological, and urogenital symptoms were found in 46%, 68%, and 74% cases, respectively. Menarche age was varied between 10 and 17-year-old. There was a significant correlation between menarche age and psychological symptoms (p=0.034). However, there was no significant correlation between menarche age and somato-vegetative as well as urogenital symptoms (p=0.257; p=0.093). Conclusion: There was a significant association between menarche age and psychological symptoms in perimenopause women. However, there was no association between menarche age and somato-vegetative as well as urogenital symptoms in perimenopause women.